2010
DOI: 10.1155/2010/273028
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy methods for detecting and imaging supported lipid bilayers

Abstract: Abstract.We have developed a Raman microspectroscopy system optimised for studying supported lipid bilayers (SLB). This system combines the benefits of Raman spectroscopy with the high spatial resolution of confocal microscopy. Furthermore, the additional incorporation of an atomic force microscope (AFM) makes it possible to directly correlate chemical information with spatial features of samples at the nanoscale. We focus on the limits of this system for detecting a single SLB and imaging its microdomains, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…In addition, classical Raman technique has a low sensitivity. This disadvantage was confirmed in other reports, and therefore, the study of such a membrane model via Raman spectroscopy is usually achieved using enhancement techniques. From our result, we concluded that the signal of unilamellar SLB is not detected using classical Raman spectra. The Raman spectra of peptides would not be broadened by SLB scattering if both species are present in the sample, and only the interactions with the SLB would influence the peptide signal.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, classical Raman technique has a low sensitivity. This disadvantage was confirmed in other reports, and therefore, the study of such a membrane model via Raman spectroscopy is usually achieved using enhancement techniques. From our result, we concluded that the signal of unilamellar SLB is not detected using classical Raman spectra. The Raman spectra of peptides would not be broadened by SLB scattering if both species are present in the sample, and only the interactions with the SLB would influence the peptide signal.…”
Section: Resultssupporting
confidence: 81%
“…This disadvantage was confirmed in other reports, and therefore the study of such a membrane model via Raman spectroscopy is usually achieved 1 for peak assignment. [43][44][45] . From our result, we concluded that the signal of unilamellar SLB is not detected using classical Raman spectra.…”
Section: Characterization Of Lipidsmentioning
confidence: 99%
“…To solve this problem, a Raman microspectroscopy system that combines a Raman spectrometer and a confocal microscope has been developed to provide high spatial resolution and signal collection from small sample volumes to study SPBs. 22 Meanwhile, conventional non-resonant Raman scattering has also been used to study single supported planar lipid bilayers by taking advantage of the properties of evanescent waves. 23 However, the sensitivity and the complexity of this system can restrict its effectiveness for SPBs.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoscale topographic ''movie'' of the membrane-related processes could be explored by using in situ AFM to investigate SLB-related studies. Examining SLBs of increasing complexity using in situ AFM has the following advantages for investigating membranerelated processes: (i) the membrane-related processes can be visualized under physiological conditions; (ii) the membranerelated processes can be monitored by time-lapse imaging, which can even provide quantitative analysis of specific characterization; (iii) AFM has high lateral resolution (in the sub-nanometre scale) and the lipid phase separation is wellstudied; (iv) the effects of lipid composition and phase can be easily investigated by changing the lipid composition and ratio in the SLB preparation; (v) AFM can be easily coupled with other surface spectroscopic (fourier transform infrared spectroscopy, 141 tip enhanced Raman spectroscopy, 142 fluorescence correlation spectroscopy, 143 etc.) or microscopic techniques (Epi-fluorescence microscopy, 144 TIRFM, 54 etc.…”
Section: Discussionmentioning
confidence: 99%